Cubic MgO powders prepared by antisolvent crystallization and reduction thermal decomposition method - QU Sheng; JIANG Lixin; YU Jingkun (Fenmo yejin jishu)
Near-nanometer cubic MgO powders were prepared by the antisolvent crystallization method combined with the reduction thermal decomposition method. The precursor powders were prepared by anhydrous ethanol and magnesium sulfate aqueous solutions with the different initial concentration. The precursor was mixed with carbon powders in different mass fraction and then subjected to the reduction thermal decomposition reaction at 800 ℃, thereby obtaining the cubic MgO powders. The results show that, by adjusting the concentration of magnesium sulfate aqueous solution, the particle size, dispersion, and sphericity of the prepared MgSO4 precursor can be effectively controlled. When the initial concentration of magnesium sulfate aqueous solution is 0.1 mol/L, the particle size of the precursor is the smallest (the average particle size is 1.21 μm), the dispersion is the best, and the microstructure is nearly spherical. During the thermal decomposition process, the smaller the precursor particle size, the closer the morphology is spherical, the higher the amount of carbon powders added, and the higher the conversion rate of MgO. When the mass ratio of the precursor to carbon powders is 2:1, the cubic MgO powders with high purity can be prepared.